JEJARING USAHA “RASENDRIYA KRIYA TULANG DAUN” SEBAGAI STRATEGI KEBERLANJUTAN PROGRAM PENGEMBANGAN USAHA PRODUK INTELEKTUAL KAMPUS - Amin RETNONINGSIH; Widowati Widowati; Muhammad KHAFID; Sucihatiningsih Dian Wisika PRAJANTI (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2021)
Woody tree leaves have diverse shapes and repeats. The skeleton leaves in the woody plant group are quite strong and have a unique shape so that they can become as the raw material for making exclusive crafts. Raw materials of skeleton leaves have been used by the business unit "Rasendriya Kriya Tulang Daun" as the main ingredient in making six types of crafts. This business unit was born from the service community of the Campus Intellectual Product Development Program (PPUPIK) at Universitas Negeri Semarang (UNNES). In addition to producing crafts, Rasendriya also provides training services ranging from the manufacturing and coloring of skeleton leaf to make craft products. Rasendriya's goal is to become an innovative business unit that is able to motivate students to become entrepreneurs while contributing income generating for UNNES. One of the craft products that is in great demand by consumers is painting on skeleton leaves. This product marketing can reach various consumers from individuals to government and private institutions. The key to successful marketing is a wide network of institutions such as banks, the Department of Trade and the Office of Cooperatives. These institutions routinely provide training to improve managerial skills and facilitate exhibitions for promotion so that Rasendriya products are widely known at local, national and international events, as well as they become customers of painting products on skeleton leaves as souvenirs of the company/institution. An extensive network encourages Rasendriya to continue to increase the quantity of quality products so that the sustainability of the campus business as income generating can be predicted. Daun pohon berkayu memiliki bentuk dan pertulangan yang beranekaragaman. Tulang daun pada kelompok tanaman tersebut cukup kuat dan bentuknya unik sehingga dapat menjadi bahan baku pembuatan kriya/kerajinan yang eksklusif. Bahan baku tulang daun telah digunakan unit usaha “Rasendriya Kriya Tulang Daun” sebagai bahan utama pembuatan enam jenis kriya. Unit usaha ini lahir dari skema pengabdian Program Pengembangan Usaha Produk Intelektual Kampus (PPUPIK) di Universitas Negeri Semarang (UNNES). Selain memproduksi kriya, Rasendriya juga menyediakan jasa pelatihan mulai dari pembuatan dan pewarnaan tulang daun hingga pembuatan produk kriya. Tujuan Rasendriya adalah menjadi unit usaha inovatif yang mampu memotivasi mahasiswa menjadi wirausaha sekaligus memberikan kontribusi income generating untuk UNNES. Salah satu produk kriya yang sangat diminati konsumen adalah lukisan di atas tulang daun. Pemasaran produk ini dapat menjangkau berbagai lapisan konsumen mulai perseorangan hingga lembaga pemerintah maupun swasta. Kunci keberhasilan pemasarannya adalah jejaring yang luas dengan berbagai lembaga yang relevan seperti bank, Dinas Perdagangan dan Dinas Koperasi. Lembaga-lembagl tersebut secara rutin memberikan pelatihan untuk meningkatkan kemampuan manajerial dan memfasilitasi pameran untuk promosi sehingga produk Rasendriya dikenal luas, baik pada event lokal, nasional, maupun internasional, sekaligus mereka menjadi pelanggan produk lukisan di atas tulang daun sebagai souvenir perusahaan/lembaga tersebut. Jejaring yang luas mendorong Rasendriya untuk terus meningkatkan kuantitas produk berkualitas sehingga keberlanjutan usaha kampus sebagai income generating dapat diprediksikan.